Optimalisasi Konten Instagram dan TikTok serta Pelatihan Editing Video dengan CapCut bagi Masyarakat - Anang Setiawan; Fadil Muhammad; Nurul Chalisa Majiding; Achmad Ridha; Azlan Azhari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The training on optimizing Instagram and TikTok social media content and video editing using the CapCut application was part of a community service program aimed at enhancing digital literacy and visual content production skills. This activity took place during the Education Exhibition commemorating the 63rd Anniversary of Universitas Negeri Makassar, involving participants from various backgrounds, including students and small business owners. Using a participatory method combining theoretical sessions, demonstrations, and hands-on practice, the training resulted in significant improvements in participants’ understanding of social media strategies, personal branding, and video editing skills. Evaluation results showed a 41% increase from pre-test to post-test scores, and 85% of participants grasped the basic concepts of reach and engagement in social media algorithms. This program successfully equipped participants with relevant digital competencies and contributed to social transformation through the strategic and creative use of social media.